General Sales Tax and its Role in Public Revenuse in Jordan for the Duration (1998-2012) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research aims to introduce the general tax on sales in gordan and the most important concepts related to this type of taxes and identify the  most  on characteristics and stand on its role in supplying the general budget of the necessary fundig to cover the over head of the state and the factorsinfluencing it and whether such a tax has been able to chieve the desired goals.including in contribute to an important and growing role in puplic revenues or not to be able to achieve these goals through the use of descriptive and analytical technique based on the data and information relevant.wasreached some conclusion and  recommendations was most important is that the general sales tax comes infirst place in terms of relative importance in the tax structure and Jordan formed revenues major source to finance th general budget. Contributing proceed of more than one-third of research and about 40% of overall revenuse as the average for the last five years of research period.Which indicates the impotance of this tax in the financial Jordanian economy conoard to other sources of funding.The most important recommendation were,is the emphasis on keeping the necessary and basic goods and basic services are exempt from tax in line with the principle tax justice to ease the tax burden on the limited –income groups and to emplasize the need for the tax administration to encourage voluntary response to the taxpayers and enhance these tyle of self-esteem to the tax system and activate the information and investigation of taxpayers in order to reduce the incidence of tax evasion.